DEVELOPING AN INTERNAL QUALITY ASSURANCE SYSTEM MODEL FOR EDUCATIONAL INSTITUTIONS IN THE DIGITAL ERA FOR SUSTAINABILITY: CHOMTHONG SCHOOL - Atnasiao, Wanphamaporn (Journal of MCU Nakhondhat, 2026)
The objectives of this research were 1) To study the problems, needs, and guidelines for developing an internal quality assurance system in the digital era for sustainability; 2) To develop an internal quality assurance system in the digital era for sustainability; 3) To implement an internal quality assurance system in the digital era for sustainability an internal quality assurance system in the digital era for sustainability; and 4) to evaluate the internal quality assurance system in the digital era for sustainability at Chomthong School. The research employed a mixed-methods approach. The research area was at Chomthong school. Key informants selected by purposive sampling for interviews were 15 informants and 70 informants for the questionnaire. Two types of research instruments were used consisting of an in-depth interview and data record and questionnaires. Data was analyzed using mean, standard deviation, and content analysis and summarized into issues. The research revealed that the problems and needs comprised policy, school quality assurance, information and digital, personnel and digital competence, curriculum, teaching, and assessment, and resources and infrastructure. The guidelines for developing an internal quality assurance system in the digital era for sustainability: Chomthong school consisted of setting educational standards for the educational institution; developing an educational management development plan focused on quality according to educational standards; implementing the educational management development plan; evaluating and monitoring the quality of education within the educational institution; following up the results of operations to ensure quality according to educational standards; and preparing a self-assessment report. 2) The model comprises principles, objectives, systems and mechanisms, evaluation, and conditions for success. 3) The five implementation results regarding policy and management, digital implementation of the PDCA quality cycle, information systems and technology, personnel participation and capacity building, and the outcomes and sustainability of an internal quality assurance system in the digital era were at the highest level ( = 4.70, S.D.= 0.45). The feasibility was at the highest level.